Effects of Chemical Fertilizer Combined with Organic Fertilizer Application on Soil Properties, Citrus Growth Physiology, and Yield - Lian-Jie Wan; Yang Tian; Man He; Yong-Qiang Zheng; Qiang Lyu; Rang-Jin Xie; Yan-Yan Ma; Lie Deng; Shi-Lai Yi (Agriculture, 2021)
Chemical fertilizer has been excessively used for high yield of citrus around the world, especially in China; meanwhile, it deteriorates the citrus orchard soil environment. To resolve the conflict, the use of organic fertilizer provides a promising solution. However, the data about organic fertilizer used in citrus orchard is rarely available. Here, four treatments including CK (no fertilizer), CF (chemical fertilizer), OF + CF (chemical fertilizer reduction combined with organic fertilizer; application of N, P2O5, K2O fertilizer and organic fertilizer is 0.564, 0.236, 0.336 and 10 kg/plant), and BF + CF (chemical fertilizer reduction combined with bioorganic fertilizer; application of N, P2O5, K2O fertilizer and bioorganic fertilizer is 0.508, 0.320, 0.310 and 10 kg/plant) were performed in a ‘Ponkan’ (Citrus reticulata Blanco) orchard to evaluate the effect of organic fertilizer on citrus yield, growth, soil properties etc. when nutrients of fertilizer of each treatment were equal except CK. The data obtained in 2019 and 2020 showed that both OF + CF and BF + CF were beneficial to improve soil fertility (soil physicochemical and microbe properties) and citrus growth physiology (growth, nutrient and photosynthesis), alleviate NO3−-N leaching, and promote yields. Comprehensive evaluation indicated that BF + CF was more effective than OF + CF. Together, organic fertilizer has the potential to substitute partial chemical fertilizer with improvement in soil properties, growth physiology, and yield of citrus.